Pengaruh Penambahan Pure Ubi Cilembu (Ipomoea batatas L.) terhadap Sifat Fisikokimia Yoghurt Sinbiotik - Premy Puspitawati Rahayu; Cut Tasya Nur Laylita; Mulia Winirsya Apriliyani; Citra Nurma Yunita (AgriMalS, 2026)
Yogurt is a processed dairy product resulting from the fermentation of milk by lactic acid bacteria, which are responsible for shaping its consistency, sensory profile, and functional attributes. Cilembu sweet potato puree is utilized as a natural prebiotic source due to its inulin and oligosaccharide content, which have the potential to enhance the growth and viability of beneficial bacteria. This study aimed to determine the optimal level of Cilembu sweet potato puree addition in the production of synbiotic yogurt based on physicochemical parameters, including viscosity, syneresis, water holding capacity, pH, and titratable acidity. The research was conducted using an experimental approach with a Completely Randomized Design (CRD) comprising four treatment groups and five replications. The treatments consisted of P0 (control without the addition of puree), P1 (5%), P2 (10%), and P3 (15%) of Cilembu sweet potato puree calculated based on the weight of fresh milk. The data analysis was performed using a one-way Analysis of Variance (ANOVA) to assess the effect of the treatments. When significant differences were observed, Duncan’s Multiple Range Test was applied as a post hoc analysis to compare the means. The findings showed that incorporating Cilembu sweet potato puree had a significant effect (P < 0.05) on syneresis and water holding capacity, while no significant differences were observed in the other parameters. The best treatment was observed at 15% puree addition, resulting in a syneresis value of 43.46% and a water holding capacity (WHC) of 56.30%. In conclusion, the incorporation of Cilembu sweet potato puree up to 15% effectively improved the stability of synbiotic yogurt, particularly by enhancing water holding capacity and reducing syneresis.